2012
DOI: 10.1111/j.1365-2044.2012.07161.x
|View full text |Cite
|
Sign up to set email alerts
|

Emergency capnography monitoring: comparing ergonomic design of intensive care unit ventilator interfaces and specific training of staff in reducing time to activation

Abstract: Summary Modern ventilators provide capnography monitoring in patients with tracheal tubes, in compliance with national and international recommendations. This technology is often not used when patients’ lungs are non‐invasively ventilated; however, it should be accessed immediately following tracheal intubation to confirm tube placement. This study assessed the effect of ventilation interface design on the speed with which capnography can be activated by comparing the Dräger Evita 4 and Dräger V500 before and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This approach adds additional time and costs to the reporting system, but these organisations believe it provides return on investment as part of the information gathering for their safety management systems. Although efforts have begun to address some of the problem areas identified in NAP4 – for instance, wider use of capnography in emergency situations , national strategies for managing patients with tracheostomies and for the management of tracheal extubation , only the last mentioned mentions human factors, and even then only in passing. We believe that a greater emphasis on human factors will allow the technical aspects of care to be applied even more successfully.…”
Section: Discussionmentioning
confidence: 99%
“…This approach adds additional time and costs to the reporting system, but these organisations believe it provides return on investment as part of the information gathering for their safety management systems. Although efforts have begun to address some of the problem areas identified in NAP4 – for instance, wider use of capnography in emergency situations , national strategies for managing patients with tracheostomies and for the management of tracheal extubation , only the last mentioned mentions human factors, and even then only in passing. We believe that a greater emphasis on human factors will allow the technical aspects of care to be applied even more successfully.…”
Section: Discussionmentioning
confidence: 99%
“…Several ergonomic studies of ventilators have demonstrated that the manufacturer should pay more intention to ergonomic design of ventilator user interfaces. For instance, Hodges [34] studied the speed and ability of nursing and medical staff to successfully activate capnography before and after a specific episode of training and assessment, finding that the ergonomic design of the ventilator user interface affects capnography activation. Marjanovic [35] used psycho-cognitive scales (system usability scale and mental workload) and physiological measurements (pupil diameter, heart and respiratory rate, and thoracic volume variations) to assess 20 senior ICU physicians completing 11 specific tasks for each ventilator, finding that some ventilators show low ergonomics performance and a high risk of user errors.…”
Section: Discussionmentioning
confidence: 99%
“…Capnography units should be a default in future intensive care ventilators because the current direction of thought favors their use in ICUs. 40 Training in the ICUs should include methods of avoiding contamination of carbon dioxide-measuring sensors with secretions and interpretation of capnography waveforms. Anesthesiologists are better equipped with capnography knowledge and logically should be the forerunners in helping to deploy capnography outside of the operating rooms in their respective institutions.…”
Section: Future Of Capnographymentioning
confidence: 99%